Field-reversal versus self-reversal hypothesis: Alterations of the Fe-Ti magnetic minerals and an origin of reversed RM of volcanics - ORLICKÝ, Oto (Contributions to Geophysics and Geodesy, 2008)
A study has been conducted for the relation among the processes, mainly the so called maghemitization of Fe-Ti magnetic minerals, origin of remanent magnetization (RM) and the self-reversed RM of the Neogene intermediate volcanics. The presented suggestions are based mainly on previous laboratory induced self-reversed partial thermoremanent magnetization (PTRM) of the Neogene andesites and rhyolites from about 177 localities. The results have shown that the dominant carriers of magnetic properties are the products of the maghemitization of original titanomagnetites (Ti-Mt) in the Neogene intermediate rocks. From all so far obtained results, including those published in this article, it is evident that the self-reversed PTRM was acquired only by the samples which possessed the two magnetic Fe-Ti phases evidenced by the Curie temperatures. One Fe-Ti phase with the TC ≈ 555 to 585°C contained also an original phase. This, the so called titanomaghemite (Ti-Mgh) phase was created due to maghemitization of the original Ti-Mt and in most cases it has carried by in situ state reversed RM of chemico-viscous (CVRM) origin. The Ti-Mgh phase was nearly disappeared and the original Ti-Mt phase was revealed after heating of the sample to 700°C and successive cooling – on the cooling thermomagnetic curve. The self-reversed CVRM and in laboratory field induced PTRM was acquired by the rocks by the magnetostatic interactions between these two magnetic phases. In this process, the second magnetic titanomaghemite (Ti-Mgh) phase must start in the so called superparamagnetic (SP) state. When maghemitization takes place in nature, the exterior of the Fe-Ti grain being more highly oxidized compared to the interior core. The properties of the core are similar to the starting material apart from those resulting from a change in composition alone.